A rare cause of secondary amenorrhoea due to acquired cervical atresia: a case report and review of literature - Shukla, Swarnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Haematotrachelos, also known as haematocervix, is an extremely rare gynaecological condition characterised by accumulation of menstrual blood within the cervical canal due to obstruction of the cervical os. It represents one of the least common forms of genital outflow tract obstruction. We report a 41-year-old multiparous woman presenting with progressive hypomenorrhoea followed by secondary amenorrhoea and acute pelvic pain. Clinical examination revealed a ballooned cervix with a pinpoint external os. Ultrasonography and magnetic resonance imaging confirmed haematotrachelos with associated haematometrocolpos. The patient was successfully managed using a conservative uterus-preserving approach including cruciate cervical incision, serial dilatation, drainage of retained blood, Foley catheter placement intrauterine copper device insertion and adjunct hormonal therapy. Complete resolution of symptoms and restoration of regular menstrual cycles were achieved.